Formation of Transient Anionic Metal Clusters in Palladium/Diene‐Catalyzed Cross‐Coupling Reactions - Kolter, Marlene (Chemistry, 2019)
Despite their considerable practical value, palladium/1,3‐diene‐catalyzed cross‐coupling reactions between Grignard reagents RMgCl and alkyl halides AlkylX remain mechanistically poorly understood. Herein, we probe the intermediates formed in these reactions by a combination of electrospray‐ionization mass spectrometry, UV/Vis spectroscopy, and NMR spectroscopy. According to our results and in line with previous hypotheses, the first step of the catalytic cycle brings about transmetalation to afford organopalladate anions. These organopalladate anions apparently undergo S(N)2‐type reactions with the AlkylX coupling partner. The resulting neutral complexes then release the cross‐coupling products by reductive elimination. In gas‐phase fragmentation experiments, the occurrence of reductive eliminations was observed for anionic analogues of the neutral complexes. Although the actual catalytic cycle is supposed to involve chiefly mononuclear palladium species, anionic palladium nanoclusters [Pd(n)R(DE)(n)](−), (n=2, 4, 6; DE=diene) were also observed. At short reaction times, the dinuclear complexes usually predominated, whereas at longer times the tetra‐ and hexanuclear clusters became relatively more abundant. In parallel, the formation of palladium black pointed to continued aggregation processes. Thus, the present study directly shows dynamic behavior of the palladium/diene catalyst system and degradation of the active catalyst with increasing reaction time.